2023
DOI: 10.3390/jcm12020498
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Prognostic Significance of the Body Mass Index in Idiopathic Pulmonary Fibrosis

Abstract: The identification of novel prognostic biomarkers might enhance individualized management strategies in patients with idiopathic pulmonary fibrosis (IPF). Although several patient characteristics are currently used to predict outcomes, the prognostic significance of the body mass index (BMI), a surrogate measure of excess fat mass, has not been specifically investigated until recently. We systematically searched PubMed, Web of Science, and Scopus, from inception to July 2022, for studies investigating associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…It has previously been reported that there is no association between age and BMI with CPa9-HNE serum levels [16], which is in line with observations in this study when data were available. Previously, low BMI has been related to disease severity in COPD in addition to progression, risk of hospitalization, mortality, and tolerability to certain therapies in IPF [42,43]. Thus, a limitation of this study includes the lack of BMI data for the IPF and healthy participant group, even though current data do not indicate this.…”
Section: Discussionmentioning
confidence: 79%
“…It has previously been reported that there is no association between age and BMI with CPa9-HNE serum levels [16], which is in line with observations in this study when data were available. Previously, low BMI has been related to disease severity in COPD in addition to progression, risk of hospitalization, mortality, and tolerability to certain therapies in IPF [42,43]. Thus, a limitation of this study includes the lack of BMI data for the IPF and healthy participant group, even though current data do not indicate this.…”
Section: Discussionmentioning
confidence: 79%
“…Patients with chronic lung diseases often exhibit a clinical course characterized by progressive weight loss and muscle mass reduction [ 10 , 37 ] due to increased energy expenditure associated with respiratory impairment, which can lead to malnutrition [ 10 ]. The deterioration in the nutritional status caused by IPF can result in a reduction in muscle mass, impacting swallowing and necessitating feeding adaptations.…”
Section: Discussionmentioning
confidence: 99%